Pengembangan Sistem Informasi Penyewaan Gedung Berbasis Web dengan Metode Rational Unified Process (RUP) (Studi Kasus: Wisma Rata Medan) - David Josua Hutahaean; Niken Hendrakusma Wardani; Welly Purnomo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2019)
Wisma Rata is one of the buildings rental providers which can be used for wedding events, traditional events and similar events in Medan city, North Sumatra. Wisma Rata still uses a ledger in the data recording process. Although the data that have been stored in the ledger are considered sufficient for now, however the process of managing the reservation data and search the availability schedule of the building cause problem in finding data which are not efficient. Data storage is also not safe because the risk of possibility that the data being lost is very high. Another problem faced is the prospective customer must come directly to the office or must call just to find the information or check the availability of the building according to the desired day. Cause of those problems, the given solution is an building reservation information system that can help the process of building rental reservation, check on the building availability, store the reservation data, and recap the reservation data. Rational Unified Process (RUP) method is used when building the system with the phase of inception, elaboration, construction, and transition. The developed information system gets the results of validation testing with 100% valid results and compability testing with the result that the system can be accessed in different browsers. User Acceptance testing is then tested on five correspondents from each user showing that the information system of building reservation is well received by the user.